Strategi Guru Dalam Meningkatkan Pengembangan Pembelajaran PAI - Eva Safitri; Ema Pariati; Eko Nursalim (An-Nafis: Jurnal Ilmiah Keislaman dan Kemasyarakatan, 2023)
Islamic Religious Education (IRE) in vocational high schools (SMK), such as SMK Negeri 1 Karangan, plays a central role in shaping the character and morals of students. IRE teachers at SMK Negeri 1 Karangan have a significant responsibility in enhancing the quality of IRE instruction. This article discusses various strategies employed by IRE teachers to improve the development of IRE learning, including the implementation of interactive methods, utilization of technology, relevance of materials to students' lives, collaboration with external resources, facilitating open discussions on religious issues, formative assessment, and feedback usage. Furthermore, this article also encompasses the evaluation and development process of the IRE curriculum at SMK Negeri 1 Karangan, involving goal analysis, learning material evaluation, teaching methods, assessment of learning outcomes, feedback from students and teachers, identification of development needs, curriculum development, as well as implementation and monitoring phases. The aim of this evaluation and development is to ensure that Islamic religious education at SMK Negeri 1 Karangan remains in accordance, relevant, and effective according to student demands and societal developments.